Bridges in the Ancient Mediterranean - Falke, Anna Klara,; Neitmann, Florian,; Simić, Aleksandar, (Mittelmeerstudien ;, 2025)
For thousands of years, bridges have been built to overcome natural obstacles, facilitating communication, transport and military campaigns. In addition to these central infrastructural functions, bridges can be charged with other meanings, e.g. in religious contexts or as reflecting the relationship between humans and their environment. The present volume sheds light on the diversity of ancient bridges in the Mediterranean and their cultural significance, thus complementing research on ancient roads. The individual contributions offer in-depth insights into the functions and perceptions of ancient bridges in several regions and periods and combine archaeological, historical, philological, and philosophical research. With its wide range of topics and approaches, this collection brings together different perspectives on ancient bridges and inspires new transdisciplinary approaches to future research.